Relacje Polska–Rosja–Ukraina a zmieniający się ład międzynarodowy - Rotfeld, Adam Daniel (Sprawy Międzynarodowe, 2018)
To correctly understand relations between Russia, Poland and Ukraine, it is essential that Russia’s president focuses attention, not on shaping a new world order, but on establishing a political system that will ensure his long-term authoritarian governance, a system without alternatives accepted by the society. This kind of system is presented as Russia’s own original model of governance. Russia’s goal for Poland and Ukraine is to restore the international system based on ‘zones of inﬂuence’ for global powers. The international security system in the transitory period is quite often characterised by uncertainty, instability and a certain level of imbalance, leading to political unpredictability. Under these conditions, the old threats have not disappeared, but there are no new effective mechanisms and procedures to prevent and counteract new risks and challenges. These include the inspired secessions and rebellion wars that destabilise and weaken countries, and allow for achieving political, economic and military aims per procura – without involving your own armed forces in the territory of a state, against whom these measures are addressed. This requires managing executive groups of both transatlantic security and defence organisations to adopt innovative thinking. The starting point for effective implementation of the common strategy for building sustainable peace and security in Europe should be a common perception and understanding of threats by all countries of the transatlantic community. In the second decade of the 21st century, the major threats for international security are of a non-conventional nature. They appear primarily within nations and not between them. The source of these threats lies in violating democratic rules of governance and in trampling on universal values, as deﬁned by Karl Deutsch more than 50 years ago for a pluralistic security community. Politicians have the right to expect thinkers, scholars and independent intellectuals to give answers and recommendations about how to respond qualitatively to new risks, threats and challenges.